Business Feasibility Study for The Development of Plywood Plant PT. X in Lumajang - Andrew Andrew (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Plywood Factory PT. X has a problem about whether the business development plan can provide viability for the company in the future. The purpose of the study was to determine the feasibility of developing the Plywood Factory business of PT. X in Lumajang in Legal Aspects, Market and Marketing Aspects, Technical and Operational Aspects, Management and Human Resources Aspects, and Financial Aspects. The research uses qualitative with interview techniques. The research sample used Saturation Sampling obtained by 1 owner from PT. X and 1 expert in the field of plywood. The result is that legal aspect is still not equipped by PT. X so it is considered not yet worthy of development. Creation of STP and 4P for market and marketing aspects. A technical and operational aspect is carried out analysis of the location of the business development, materials, machines and the required layout. Aspects of management and resources created an organizational structure and new SOPs to support development. Financial aspects are created financial scenario. Scenario 1 with only 100% local trade results in a negative value. Scenario 2 of 50% local trade and 50% of exports results in an increase of 43%. Scenario 3 of 100% export trade resulted in an increase of 291%. Based on these calculations, scenario 1 is declared unfeasible because it is considered detrimental to the company.